Designing Cisco network service architectures (ARCH) : foundation learning guide - Tiso, John.; Hutton, Keith (Indianapolis, IN 46240 USA : Cisco Press, 2012)
This edition teaches you the latest development in network design and technologies, including network infrastructure, intelligent network services and converged network solutions.
Rev. ed. of: Authorized self-study guide / Hutton, Keith. 2009. 2nd ed.
Includes bibliographical references and index.
uaj 29/11/2013
Loans
Keywords: Computer network architectures; Computer networks; Internetworking (Telecommunication)